Laminate and method for producing same
Through the stacked thermal conductivity particle structure arranged separately at predetermined intervals on the substrate, the problem of insufficient thermal conductivity of materials such as silicon is solved, and high thermal conductivity and reliability are improved, which is suitable for thermal management of electronic equipment.
Patent Information
- Application Number
- CN202380041296.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-08
- Filing Date
- 2023-05-25
- Publication Date
- 2024-12-27
AI Technical Summary
In the prior art, it is difficult for materials such as silicon in the exothermic structure to achieve high thermal conductivity through metal bonding, and there is a problem of insufficient thermal conductivity.
A laminated structure is adopted, in which the first thermally conductive particles arranged separately at predetermined intervals on the substrate form contact with the second thermally conductive particles, the volume average particle size of the first thermally conductive particles is smaller than the second thermally conductive particles, and a multi-layer structure is formed on the substrate. To improve thermal conductivity, the stacking arrangement of copper, silver coated particles and low melting point metal particles are included.
It has achieved the improvement of high thermal conductivity and reliability, is suitable for thermal management of electronic equipment, and improves the thermal conductivity and reliability of the stacked body.
Smart Images

Figure CN119212867A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a laminate and a method for producing the laminate. Background Art
[0002] In LSI (Large Scale Integration) and other electronic devices, if the LSI itself is exposed to high temperature for a long time due to the heat generated by the components used, there is a concern that it may cause malfunction or failure. Therefore, in order to prevent the temperature rise of LSI and the like, thermal conductive materials are widely used. The thermal conductive materials can prevent the temperature rise of the device by diffusing or conducting the heat generated by the components to a heat dissipation component for dissipating the heat to the outside of the system such as the atmosphere.
[0003] If metal or ceramic is used as such a thermal conductive material, it is difficult to reduce weight, has poor processability, or has low flexibility. Therefore, various thermal conductive materials using polymer materials such as resins and rubbers as base materials have been proposed.
[0004] For example, a thermally conductive adhesive has been proposed, which includes a thermosetting adhesive containing a curing component and a curing agent for the curing component, and a metal filler dispersed in the thermosetting adhesive, the metal filler including silver powder and solder powder, the solder powder exhibiting a melting temperature lower than the heat curing treatment temperature of the thermally conductive adhesive and reacting with the silver powder under the heat curing treatment conditions of the thermosetting adhesive to generate a high melting point solder alloy exhibiting a melting point higher than the melting temperature of the solder powder, the curing agent being a curing agent having flux activity for the metal filler, the curing component being a glycidyl ether type epoxy resin, and the curing agent being a monoanhydride of a tricarboxylic acid (for example, refer to Patent Document 1).
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent No. 5796242 Summary of the invention
[0008] Problems to be solved by the invention
[0009] However, in the prior art described in Patent Document 1, the heat dissipation module in the heat dissipation structure can achieve high thermal conductivity through metal bonding. However, the heat generating elements (electronic components) in the heat dissipation structure are often made of silicon or the like, and there is a problem that it is difficult to achieve high thermal conductivity by metal bonding.
[0010] The present invention aims to solve the above-mentioned problems and achieve the following objectives: That is, the present invention aims to provide a laminate and a method for producing the laminate that can achieve high thermal conductivity and improve reliability.
[0011] Methods used to solve problems
[0012] The method for solving the above-mentioned problem is as follows.
[0013] <1> A laminated body, comprising:
[0014] Base material;
[0015] On the substrate, a first particle arrangement layer includes first heat-conductive particles, wherein the first heat-conductive particles are arranged at predetermined intervals; and
[0016] The second particle arrangement layer includes second heat-conductive particles on the first particle arrangement layer, wherein the second heat-conductive particles are arranged at predetermined intervals.
[0017] A portion of the first heat-conductive particles included in the first particle arrangement layer is in contact with a portion of the second heat-conductive particles included in the second particle arrangement layer, and a volume average particle size of the first heat-conductive particles is smaller than a volume average particle size of the second heat-conductive particles.
[0018] The substrate includes at least one selected from silicon, aluminum, tungsten, molybdenum, glass, molding resin, stainless steel, and ceramics.
[0019] <2> The laminate according to <1>, wherein a ratio (A:B) of a volume average particle size A of the first heat conductive particles to a volume average particle size B of the second heat conductive particles is 1:2 to 1:50.
[0020] <3> The laminate according to <1> or <2>, wherein the first thermally conductive particles have a volume average particle size of 0.3 μm to 30 μm.
[0021] <4> The laminated body according to any one of <1> to <3>, wherein the second heat conductive particles have a volume average particle size of 1 μm to 100 μm.
[0022] <5> The laminate according to any one of <1> to <4>, comprising, between the substrate and the first particle arrangement layer, a third particle arrangement layer containing first low melting point metal particles, wherein the first low melting point metal particles are arranged at predetermined intervals.
[0023] <6> The laminate according to any one of <1> to <5>, comprising, between the first particle arrangement layer and the second particle arrangement layer, a fourth particle arrangement layer containing second low melting point metal particles, wherein the second low melting point metal particles are arranged at predetermined intervals.
[0024] <7> The laminated body according to any one of <1> to <6>, wherein the first heat-conductive particles and the second heat-conductive particles are at least any one of copper particles, silver-coated particles, and silver particles.
[0025] <8> The laminate according to any one of <5> to <7>, wherein the first low-melting-point metal particles include Sn and at least one selected from Bi, Ag, Cu, and In.
[0026] <9> The laminate according to <6> or <7>, wherein the second low-melting-point metal particles include Sn and at least one selected from Bi, Ag, Cu, and In.
[0027] <10> The laminate according to any one of <1> to <8> above, comprising an opposing substrate on the second particle arrangement layer that opposes the substrate,
[0028] The opposing substrate includes at least one selected from the group consisting of copper, gold, platinum, palladium, silver, zinc, iron, tin, nickel, magnesium, indium, and alloys thereof.
[0029] <11> A method for producing a laminate, comprising the following steps:
[0030] a first particle arrangement layer forming step of forming a first particle arrangement layer including first thermally conductive particles arranged and spaced apart at predetermined intervals on a substrate; and
[0031] a second particle arrangement layer forming step of forming a second particle arrangement layer including second heat conductive particles arranged and spaced apart at predetermined intervals on the first particle arrangement layer;
[0032] The substrate includes at least one selected from silicon, aluminum, tungsten, molybdenum, glass, molding resin, stainless steel, and ceramics.
[0033] Effects of the Invention
[0034] According to the present invention, the above-mentioned various problems of the prior art can be solved, the above-mentioned objects can be achieved, and a laminated body and a method for manufacturing the laminated body that can realize high thermal conductivity and improve reliability can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 It is a schematic diagram showing an example of the laminated body according to the first embodiment.
[0036] Figure 2 It is a schematic diagram showing an example of a laminated body according to the second embodiment.
[0037] Figure 3 It is a schematic diagram showing an example of a laminated body according to the third embodiment.
[0038] Figure 4 This is a schematic cross-sectional view showing an example of a heat dissipation structure used in the present invention. DETAILED DESCRIPTION
[0039] (Laminated body)
[0040] The laminate of the present invention comprises a substrate, a first particle arrangement layer, and a second particle arrangement layer, and preferably comprises a third particle arrangement layer and a fourth particle arrangement layer, and further comprises other layers as necessary.
[0041] In the present invention, by having: a substrate; a first particle arrangement layer on the substrate containing first heat-conductive particles, wherein the first heat-conductive particles are arranged at predetermined intervals; and a second particle arrangement layer on the first particle arrangement layer containing second heat-conductive particles, wherein the second heat-conductive particles are arranged at predetermined intervals, a vertical heat-conductive path can be efficiently formed, and even if the substrate is formed of at least one selected from silicon, aluminum, tungsten, molybdenum, glass, molding resin, stainless steel and ceramic and has poor solder wettability, low thermal resistance and excellent stress relaxation can be achieved, high thermal conductivity can be achieved, and reliability can be greatly improved.
[0042] <Base material>
[0043] The shape, structure, size, material, etc. of the substrate are not particularly limited and can be appropriately selected depending on the purpose.
[0044] Examples of the shape of the substrate include a plate shape, a sheet shape, etc. Examples of the structure of the substrate include a single layer structure, a laminated structure, etc. The size of the substrate can be appropriately selected depending on the intended use, etc.
[0045] The material of the substrate is a material that is not easily wetted by solder, and includes at least one selected from silicon, aluminum, tungsten, molybdenum, glass, molding resin, stainless steel and ceramics. Examples of the ceramics include aluminum nitride, silicon carbide, aluminum oxide, gallium nitride, etc. Examples of the molding resin include epoxy resin, silicone resin, urethane resin, acrylic resin, etc.
[0046] The average thickness of the substrate is not particularly limited and can be appropriately selected depending on the intended purpose.
[0047] The substrate may be the heat generating element (electronic component) itself in the heat dissipating structure.
[0048] <First particle arrangement layer>
[0049] The first particle array layer contains first thermally conductive particles, preferably a binder resin, and further contains other components as necessary.
[0050] The first particle array layer is formed on the substrate, preferably in contact with the substrate, and the first thermally conductive particles are more preferably in contact with the substrate.
[0051] -First thermally conductive particle-
[0052] The first heat-conductive particles are preferably at least any one of copper particles, silver-coated particles, and silver particles.
[0053] Examples of the silver-coated particles include silver-coated copper particles, silver-coated nickel particles, and silver-coated aluminum particles.
[0054] The shape of the first heat conductive particles is not particularly limited and can be appropriately selected depending on the intended purpose. Examples thereof include spherical, flat, granular, and needle-like shapes.
[0055] The first thermally conductive particles preferably have a volume average particle size of 0.3 μm to 30 μm, more preferably 0.5 μm to 10 μm. When the volume average particle size of the thermally conductive particles is 0.3 μm to 30 μm, high thermal conductivity and low thermal resistance can be achieved.
[0056] The volume average particle size can be measured, for example, using a laser diffraction and scattering particle size distribution measuring device (product name: Microtrac MT3300EXII).
[0057] -Binder resin-
[0058] The binder resin contains a film-forming resin, a curable resin, and a curing agent.
[0059] As the above-mentioned film-forming resin, there is no particular limitation and it can be appropriately selected according to the purpose, and for example, phenoxy resin, unsaturated polyester resin, saturated polyester resin, urethane resin, butadiene resin, polyimide resin, polyamide resin, polyolefin resin, etc. can be mentioned. They can be used alone or in combination of two or more.
[0060] The curable resin is not particularly limited and can be appropriately selected depending on the intended purpose. Examples thereof include epoxy resins, oxetane compounds, and (meth)acrylates.
[0061] -Epoxy resin-
[0062] As the above-mentioned epoxy resin, there is no particular restriction, and it can be appropriately selected according to the purpose, and for example, glycidyl ether type epoxy resin, phenol novolac type epoxy resin, cresol novolac type epoxy resin, bisphenol A type epoxy resin, trisphenol type epoxy resin, tetraphenol type epoxy resin, phenol-xylylene type epoxy resin, naphthol-xylylene type epoxy resin, phenol-naphthol type epoxy resin, phenol-dicyclopentadiene type epoxy resin, alicyclic epoxy resin, aliphatic epoxy resin, etc. can be mentioned. They can be used alone or in combination of two or more.
[0063] -Oxetane compounds-
[0064] The oxetane compound is a compound having an oxetane group, and may be an aliphatic compound, an alicyclic compound, or an aromatic compound.
[0065] The oxetane compound may be a monofunctional oxetane compound having only one oxetane group, or may be a polyfunctional oxetane compound having two or more oxetane groups.
[0066] The oxetane compound is not particularly limited and can be appropriately selected according to the purpose. For example, 3,7-bis(3-oxetanyl)-5-oxa-nonane, 1,4-bis[(3-ethyl-3-oxetanylmethoxy)methyl]benzene, 1,2-bis[(3-ethyl-3-oxetanylmethoxy)methyl]ethane, 1,3-bis[(3-ethyl-3-oxetanylmethoxy)methyl]propane, ethylene glycol bis(3-ethyl-3-oxetanylmethyl)ether, triethylene glycol bis(3-ethyl-3-oxetanylmethyl)ether, tetraethylene glycol bis(3-ethyl-3-oxetanylmethyl)ether, 1,4-bis(3-ethyl-3-oxetanylmethoxy)butane, 1 ,6-bis(3-ethyl-3-oxetanylmethoxy)hexane, 3-ethyl-3-(phenoxy)methyloxetane, 3-ethyl-3-(cyclohexyloxymethyl)oxetane, 3-ethyl-3-(2-ethylhexyloxymethyl)oxetane, 3-ethyl-3-hydroxymethyloxetane, 3-ethyl-3-(chloromethyl)oxetane, 3-ethyl-3{[(3-ethyloxetane-3-yl)methoxy]methyl}oxetane, xylylenebisoxetane, 4,4'-bis[(3-ethyl-3-oxetanyl)methoxymethyl]biphenyl (OXBP), isophthalic acid bis[(3-ethyl-3-oxetanyl)methyl]ester (OXIPA), etc. These may be used alone or in combination of two or more.
[0067] -(Meth)acrylate-
[0068] As the above-mentioned (meth) acrylate, there is no particular limitation, and it can be appropriately selected according to the purpose, and for example, methacrylate, ethyl acrylate, isopropyl acrylate, isobutyl acrylate, phosphate acrylate, epoxy acrylate, ethylene glycol diacrylate, diethylene glycol diacrylate, trimethylolpropane triacrylate, dimethylol tricyclodecane diacrylate, 1,4-butanediol tetraacrylate, 2-hydroxy-1,3-diacryloxy propane, 2,2-bis [4- (acryloxymethoxy) phenyl] propane, 2,2-bis [4- (acryloxyethoxy) phenyl] propane, dicyclopentenyl acrylate, tricyclodecyl acrylate, tri (acryloxyethyl) isocyanurate, urethane acrylate, etc. can be mentioned. In addition, it is also possible to cite that these acrylates are methacrylates. They can be used alone or in combination of two or more.
[0069] -Curing agent-
[0070] The curing agent is not particularly limited and can be appropriately selected depending on the intended purpose. Examples thereof include imidazoles, organic peroxides, anionic curing agents, cationic curing agents, and organic acids.
[0071] Examples of the imidazoles include 2-ethyl 4-methyl imidazole and the like.
[0072] Examples of the organic peroxide include lauroyl peroxide, butyl peroxide, benzyl peroxide, dilauroyl peroxide, dibutyl peroxide, peroxydicarbonate, and benzoyl peroxide.
[0073] Examples of the anionic curing agent include organic amines and the like.
[0074] Examples of the cationic curing agent include sulfonium salts, onium salts, and aluminum chelate agents.
[0075] Examples of the organic acid include glutaric acid, succinic acid, etc. The curing agent may be a compound modified with glutaric anhydride or succinic anhydride, or a metal salt of an organic acid such as silver glutarate.
[0076] -Other ingredients-
[0077] The first particle arrangement layer may contain other ingredients as long as it does not damage the effect of the present invention. There is no particular restriction on the other ingredients, which can be appropriately selected according to the purpose, and for example, antioxidants, ultraviolet light absorbers, curing accelerators, silane coupling agents, leveling agents, flame retardants, etc. can be mentioned.
[0078] -Arrangement state of the first heat-conductive particles-
[0079] In the present invention, the first particle arrangement layer includes the first thermally conductive particles arranged and spaced apart at predetermined intervals. It is preferred that the first thermally conductive particles are in contact with the substrate in order to achieve high thermal conductivity.
[0080] The first particle array layer includes the first heat conductive particles arranged at predetermined intervals and separated from each other. For example, the solidified material can be cut, the cut surface obtained by grinding, and the ground surface can be confirmed using a semiconductor inspection microscope or the like.
[0081] The first heat-conductive particles are preferably arranged in a regular manner in which a predetermined arrangement is repeated when the first particle arrangement layer is viewed from above. The arrangement of the first heat-conductive particles, for example, can be a square lattice arrangement when the first particle arrangement layer is viewed from above. In addition, as a regular arrangement method of the first heat-conductive particles, lattice arrangements such as rectangular lattices, rhombic lattices, hexagonal lattices, triangular lattices, etc. can be cited. In the arrangement of the first heat-conductive particles, lattices of different shapes can be combined in multiple. As a method of arranging the first heat-conductive particles, the first heat-conductive particles can arrange the particle columns arranged linearly at predetermined intervals in parallel at predetermined intervals. The areas where the first heat-conductive particles are densely arranged and the areas where they are sparsely arranged can be regularly repeated. It is preferred that the first heat-conductive particles are independently separated from each other from the perspective of improving thermal conductivity. In addition, a plurality of the first heat-conductive particles are connected or close to form a unit, and the regular arrangement of the unit is also included.
[0082] When the first heat conductive particles are regularly arranged, the lattice axis or arrangement axis of the arrangement may be parallel to or intersect at least one of the longitudinal direction of the first particle arrangement layer and a direction perpendicular to the longitudinal direction.
[0083] The distance between the first heat-conductive particles is not particularly limited and can be appropriately selected according to the purpose. For example, the closest distance between the particles is preferably 0.5 times or more, more preferably 0.7 times or more, of the volume average particle size of the first heat-conductive particles. On the other hand, the closest distance between the particles is preferably 100 times or less, more preferably 50 times or less, of the volume average particle size of the first heat-conductive particles.
[0084] The number density of the first thermally conductive particles is preferably 100 particles / mm 2 More than 300 pieces / mm 2 More than 70,000 pieces / mm 2 Below, more preferably 6,000 pieces / mm 2 Above 45,000 pieces / mm 2 the following.
[0085] The average thickness of the first heat conductive layer is not particularly limited and can be appropriately selected depending on the intended purpose, but is preferably 1 μm to 100 μm, and more preferably 1 μm to 30 μm.
[0086] <Second particle arrangement layer>
[0087] The second particle arrangement layer is formed on the first particle arrangement layer. The second particle arrangement layer includes the second thermally conductive particles arranged at predetermined intervals, preferably contains a binder resin, and further contains other components as necessary.
[0088] - Second thermally conductive particles -
[0089] As the second heat-conductive particles, at least any one of copper particles, silver-coated particles, and silver particles is preferred.
[0090] Examples of the silver-coated particles include silver-coated copper particles, silver-coated nickel particles, and silver-coated aluminum particles.
[0091] The shape of the second heat-conductive particles is not particularly limited and can be appropriately selected depending on the intended purpose. Examples thereof include spherical, flat, granular, and needle-like shapes.
[0092] It is necessary that a portion of the first heat-conductive particles included in the first particle arrangement layer is in contact with a portion of the second heat-conductive particles included in the second particle arrangement layer, and the volume average particle size of the first heat-conductive particles is smaller than the volume average particle size of the second heat-conductive particles. If the volume average particle size of the first heat-conductive particles is larger than the volume average particle size of the second heat-conductive particles, thermal conductivity may be reduced.
[0093] The ratio of the volume average particle size A of the first heat-conductive particles to the volume average particle size B of the second heat-conductive particles (A:B) is preferably 1:2 to 1:50, and more preferably 1:10 to 1:40.
[0094] The volume average particle size of the second thermally conductive particles is preferably 1 μm to 100 μm, more preferably 10 μm to 70 μm, and even more preferably 10 μm to 50 μm. If the volume average particle size of the second thermally conductive particles is 1 μm to 100 μm, high thermal conductivity and low thermal resistance can be achieved.
[0095] The volume average particle diameter of the second heat-conductive particles can be measured in the same manner as the volume average particle diameter of the first heat-conductive particles.
[0096] -Binder resin-
[0097] The binder resin in the second particle arrangement layer is the same as the binder resin in the first particle arrangement layer described above, and therefore the description thereof is omitted.
[0098] -Other ingredients-
[0099] The other components in the second particle arrangement layer are the same as those in the first particle arrangement layer described above, and thus description thereof is omitted.
[0100] -Arrangement of the second heat-conductive particles-
[0101] The arrangement state of the second heat-conductive particles is the same as the arrangement state of the first heat-conductive particles in the first particle arrangement layer, and therefore the description thereof is omitted.
[0102] The average thickness of the second heat conductive layer is not particularly limited and can be appropriately selected depending on the intended purpose, but is preferably 20 μm to 300 μm, and more preferably 20 μm to 100 μm.
[0103] <Third particle arrangement layer>
[0104] The third particle arrangement layer is preferably formed between the substrate and the first particle arrangement layer.
[0105] The third particle arrangement layer contains the first low-melting-point metal particles in a state where the first low-melting-point metal particles are separated and arranged at predetermined intervals, and preferably contains a binder resin, and further contains other components as necessary.
[0106] -1st low melting point metal particle-
[0107] As the first low melting point metal particles, solder particles specified in JIS Z3282-1999 are preferably used.
[0108] As the above-mentioned solder particles, for example, Sn-Pb solder particles, Pb-Sn-Sb solder particles, Sn-Sb solder particles, Sn-Pb-Bi solder particles, Sn-Bi solder particles, Sn-Bi-Ag solder particles, Sn-Cu solder particles, Sn-Pb-Cu solder particles, Sn-In solder particles, Sn-Ag solder particles, Sn-Pb-Ag solder particles, Pb-Ag solder particles, Sn-Ag-Cu solder particles, etc. can be cited. They can be used alone or in combination of two or more. Among these, preferably, a solder particle containing Sn and at least one selected from Bi, Ag, Cu and In is used, and more preferably, Sn-Bi solder particles, Sn-Bi-Ag solder particles, Sn-Ag-Cu solder particles, and Sn-In solder particles are used.
[0109] The shape of the first low-melting-point metal particles is not particularly limited and can be appropriately selected depending on the intended purpose. Examples thereof include spherical, flat, granular, and needle-like shapes.
[0110] The melting point of the first low-melting-point metal particles is preferably 100° C. to 250° C., and more preferably 120° C. to 200° C.
[0111] The volume average particle size of the low melting point metal particles is not particularly limited and can be appropriately selected according to the purpose, and is preferably 10 μm or less, more preferably 1 μm or more and 5 μm or less. The volume average particle size of the low melting point metal particles can be measured in the same manner as the volume average particle size of the thermally conductive particles.
[0112] -Binder resin-
[0113] The binder resin in the third particle arrangement layer is the same as the binder resin in the first particle arrangement layer described above, and therefore the description thereof is omitted.
[0114] -Other ingredients-
[0115] The other components in the third particle arrangement layer are the same as those in the first particle arrangement layer described above, and thus description thereof is omitted.
[0116] - Arrangement state of the first low melting point metal particles -
[0117] The arrangement state of the first low-melting-point metal particles is the same as the arrangement state of the first thermally conductive particles in the first particle arrangement layer described above, and therefore the description thereof is omitted.
[0118] The average thickness of the third particle arrangement layer is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 1 μm to 100 μm, and more preferably 1 μm to 50 μm.
[0119] <Fourth particle arrangement layer>
[0120] The fourth particle arrangement layer is preferably formed between the first particle arrangement layer and the second particle arrangement layer. The fourth particle arrangement layer contains the second low melting point metal particles arranged at predetermined intervals, preferably contains a binder resin, and further contains other components as needed.
[0121] -Second low melting point metal particles-
[0122] The second low-melting-point metal particles are the same as the first low-melting-point metal particles in the third particle arrangement layer, and thus description thereof is omitted.
[0123] -Binder resin-
[0124] The binder resin in the fourth particle arrangement layer is the same as the binder resin in the first particle arrangement layer, and therefore the description thereof is omitted.
[0125] -Other ingredients-
[0126] The other components in the fourth particle arrangement layer are the same as the other components in the first particle arrangement layer described above, and thus the description thereof is omitted.
[0127] -Arrangement state of the second low melting point metal particles-
[0128] The arrangement state of the second low-melting-point metal particles is the same as the arrangement state of the first thermally conductive particles in the first particle arrangement layer, and therefore the description thereof is omitted.
[0129] The average thickness of the fourth particle arrangement layer is the same as the average thickness of the third particle arrangement layer, and thus the description thereof is omitted.
[0130] <Opposing substrate>
[0131] The opposing substrate is disposed to face the substrate, and its shape, structure, size, material, etc. are not particularly limited and can be appropriately selected depending on the purpose.
[0132] Examples of the shape of the opposing substrate include a plate shape, a sheet shape, etc. Examples of the structure of the opposing substrate include a single layer structure, a laminated structure, etc. The size of the opposing substrate can be appropriately selected according to the intended use, etc.
[0133] The material of the opposing substrate is a material that is easily wetted by solder, and includes at least one selected from copper, gold, platinum, palladium, silver, zinc, iron, tin, nickel, magnesium, indium, and alloys thereof.
[0134] The average thickness of the opposing substrate is not particularly limited and can be appropriately selected depending on the intended purpose.
[0135] The opposing substrate may be the heat dissipation module itself in the heat dissipation structure.
[0136] <Other components>
[0137] The other member is not particularly limited and can be appropriately selected depending on the purpose. Examples thereof include an intermediate layer and a protective layer.
[0138] (Method for producing laminated body)
[0139] The method for producing a laminate of the present invention includes a first particle arrangement layer forming step and a second particle arrangement layer forming step, and further includes other steps as necessary.
[0140] <First particle arrangement layer forming step>
[0141] The first particle arrangement layer forming step is a step of forming a first particle arrangement layer including first heat conductive particles arranged and spaced apart at predetermined intervals on a substrate.
[0142] The substrate includes at least one selected from silicon, aluminum, tungsten, molybdenum, glass, molding resin, stainless steel, and ceramics.
[0143] The first heat-conductive particles are the same as the first heat-conductive particles included in the first particle arrangement layer, and thus description thereof is omitted.
[0144] There is no particular limitation on the method for forming the first particle arrangement layer containing the first heat-conductive particles arranged at predetermined intervals, and the method can be appropriately selected according to the purpose. For example, a mold having concave portions corresponding to the arrangement pattern of the first heat-conductive particles is prepared, the first heat-conductive particles are filled in the concave portions of the mold, a resin layer containing a binder resin formed on a release film is attached thereto, and the first heat-conductive particles are pressed in. Thus, by rotating the first heat-conductive particles in a predetermined pattern on the resin layer, the first particle arrangement layer can be formed in which the first heat-conductive particles are arranged at predetermined intervals.
[0145] Next, the first particle arrangement layer is placed on the substrate so that the first heat conductive particles are in contact with each other, and then pressed, thereby forming the first particle arrangement layer including the first heat conductive particles arranged at predetermined intervals.
[0146] <Second Particle Arrangement Layer Formation Step>
[0147] The second particle arrangement layer forming step is a step of forming the second particle arrangement layer including the second heat conductive particles arranged and spaced apart at predetermined intervals on the first particle arrangement layer.
[0148] The second heat-conductive particles are the same as the second heat-conductive particles included in the second particle arrangement layer, and thus description thereof is omitted.
[0149] The method of forming the second particle arrangement layer including the second heat conductive particles arranged at predetermined intervals is the same as the method of forming the first particle arrangement layer including the first heat conductive particles arranged at predetermined intervals, and thus the description thereof is omitted.
[0150] <Other Process>
[0151] The other steps are not particularly limited and can be appropriately selected depending on the purpose. Examples thereof include a third particle arrangement layer forming step and a fourth particle arrangement layer forming step.
[0152] Here, about the embodiment of the laminated body of the present invention, it is described in detail with reference to the accompanying drawings. In addition, in each accompanying drawing, the same component is attached with the same symbol, and repeated description is sometimes omitted. In addition, the number, position, shape, etc. of the following constituent members are not limited to the form of this implementation, and on the basis of implementing the present invention, it can become a preferred number, position, shape, etc.
[0153] <First embodiment>
[0154] Figure 11 is a schematic diagram showing an example of a laminated body according to the first embodiment. Figure 1 In the stacked body 10, there is a first particle arrangement layer 12 on a substrate 11, in which first thermally conductive particles 17 are separated and arranged at predetermined intervals, a third particle arrangement layer 14 on the above-mentioned first particle arrangement layer, in which first low-melting-point metal particles 19 are separated and arranged at predetermined intervals, a second particle arrangement layer 13 on the third particle arrangement layer, in which second thermally conductive particles 18 are separated and arranged at predetermined intervals, a fourth particle arrangement layer 15 on the second particle arrangement layer, in which second low-melting-point metal particles 20 are separated and arranged at predetermined intervals, and an opposing substrate 16 on the fourth particle arrangement layer.
[0155] Part of the first heat-conductive particles 17 included in the first particle arrangement layer 12 is in contact with part of the second heat-conductive particles 18 included in the second particle arrangement layer 13 , and the volume average particle size of the first heat-conductive particles is smaller than that of the second heat-conductive particles.
[0156] <Second embodiment>
[0157] Figure 2 2 is a schematic diagram showing an example of a laminated body according to the second embodiment. Figure 2 In the stacked body 10A, on a substrate 11, there is a first particle arrangement layer 12 in which first heat-conductive particles 17 are separated and arranged at predetermined intervals, on the above-mentioned first particle arrangement layer, there is a second particle arrangement layer 13 in which second heat-conductive particles 18 are separated and arranged at predetermined intervals, on the second particle arrangement layer, there is a fourth particle arrangement layer 15 in which second low-melting-point metal particles 20 are separated and arranged at predetermined intervals, and on the fourth particle arrangement layer, there is an opposing substrate 16.
[0158] Part of the first heat-conductive particles 17 included in the first particle arrangement layer 12 is in contact with part of the second heat-conductive particles 18 included in the second particle arrangement layer 13 , and the volume average particle size of the first heat-conductive particles is smaller than that of the second heat-conductive particles.
[0159] <Third embodiment>
[0160] Figure 3 1 is a schematic diagram showing an example of a laminated body according to the third embodiment. Figure 3 In the stacked body 10B, on a substrate 11, there is a first particle arrangement layer 12 in which first thermally conductive particles 17 are separated and arranged at predetermined intervals, on the above-mentioned first particle arrangement layer, there is a third particle arrangement layer 14 in which first low-melting-point metal particles 19 are separated and arranged at predetermined intervals, on the third particle arrangement layer, there is a second particle arrangement layer 13 in which second thermally conductive particles 18 are separated and arranged at predetermined intervals, and on the second particle arrangement layer, there is an opposing substrate 16.
[0161] Part of the first heat-conductive particles 17 included in the first particle arrangement layer 12 is in contact with part of the second heat-conductive particles 18 included in the second particle arrangement layer 13 , and the volume average particle size of the first heat-conductive particles is smaller than that of the second heat-conductive particles.
[0162] For example, the laminate of the present invention can be suitably used to form a power LED module or a power IC module by filling the tiny gap between a heat source such as an LSI and a heat sink, thereby connecting a heat dissipating substrate mounted with a thermal interface material (TIM) that allows heat to flow smoothly between the two, an LED chip or an IC chip, and a heat sink.
[0163] Here, as the power LED module, there are a module of a wire bonding mounting type and a module of a flip chip mounting type, and as the power IC module, there is a module of a wire bonding mounting type.
[0164] The heat dissipation structure used in the present invention is composed of a heat generating body, the laminated body of the present invention, and a heat dissipation member.
[0165] The heat generating element is not particularly limited and can be appropriately selected depending on the intended purpose. Examples thereof include electronic components such as a CPU (Central Processing Unit), an MPU (Micro Processing Unit), and a GPU (Graphics Processing Unit).
[0166] The heat dissipating member is not particularly limited as long as it is a structure that dissipates heat generated by an electronic component (heat generating element), and can be appropriately selected depending on the purpose. Examples thereof include heat dissipating modules, heat sinks, temperature equalizing plates, and heat pipes.
[0167] The heat dissipation module is a member for efficiently conducting the heat of the electronic component to other components. The material of the heat dissipation module is not particularly limited and can be appropriately selected according to the purpose, for example, copper, aluminum, etc. The heat dissipation module is usually in a flat plate shape.
[0168] The heat sink is a member for releasing the heat of the electronic component into the air. There is no particular limitation on the material of the heat sink, and it can be appropriately selected according to the purpose, for example, copper, aluminum, etc. The heat sink, for example, has a plurality of fins. The heat sink, for example, has a base, and a plurality of fins extending in a non-parallel direction (for example, an orthogonal direction) relative to one surface of the base.
[0169] Generally speaking, the heat dissipation module and the heat dissipation fin are solid structures without any space inside.
[0170] The temperature equalizing plate is a hollow structure. A volatile liquid is sealed in the inner space of the hollow structure. Examples of the temperature equalizing plate include a temperature equalizing plate having a hollow structure in the heat dissipation module and a hollow structure in the plate shape such as the heat sink.
[0171] The heat pipe is a hollow structure in a cylindrical, substantially cylindrical or flat cylindrical shape, and a volatile liquid is sealed in the inner space of the hollow structure.
[0172] here, Figure 4 FIG. 1 is a schematic cross-sectional view showing an example of a semiconductor device as a heat dissipation structure. The laminate 7 of the present invention dissipates the heat generated by the electronic components 3 such as semiconductor components. Figure 4 As shown, the main surface 2a fixed to the heat dissipation module 2 and facing the electronic component 3 is sandwiched between the electronic component 3 and the heat dissipation module 2. In addition, the thermally conductive sheet 1 is sandwiched between the heat dissipation module 2 and the heat dissipation sheet 5.
[0173] The heat dissipation module 2 is formed in a square plate shape, for example, and has a main surface 2a facing the electronic component 3, and a side wall 2b erected along the outer periphery of the main surface 2a. The heat dissipation module 2 is provided with a heat conductive sheet 1 on the main surface 2a surrounded by the side wall 2b, and a heat sink 5 is provided on the other surface 2c on the opposite side of the main surface 2a through the heat conductive sheet 1. The higher the thermal conductivity of the heat dissipation module 2, the lower the thermal resistance, and the heat of the electronic component 3 such as the semiconductor component is efficiently absorbed. For example, it can be formed using copper or aluminum with good thermal conductivity.
[0174] Electronic component 3 is, for example, a semiconductor component such as BGA, and is mounted on wiring board 6. In heat dissipation module 2, the front end surface of side wall 2b is mounted on wiring board 6, thereby surrounding electronic component 3 at a predetermined distance via side wall 2b.
[0175] Furthermore, by providing the laminated body 7 of the present invention on the main surface 2 a of the heat dissipation module 2 , heat generated by the electronic component 3 is absorbed, and a heat dissipation member is formed that dissipates the heat through the heat sink 5 .
[0176] Example
[0177] Hereinafter, examples of the present invention will be described, but the present invention is not limited to these examples.
[0178] (Example 1)
[0179] <Preparation of the first particle arrangement layer forming sheet>
[0180] -Preparation of the first particle array layer resin film-
[0181] A resin composition containing 56 parts by mass of an oxetane compound (4,4'-bis[(3-ethyl-3-oxetane)methoxymethyl]biphenyl, manufactured by UBE Co., Ltd.), 22 parts by mass of glutaric acid (manufactured by Tokyo Chemical Industry Co., Ltd.) and 22 parts by mass of a polyamide compound (M1276, manufactured by Arkema Co., Ltd.) was applied to a peeling film (PET38GS, manufactured by LINTEC Co., Ltd.) to produce a resin film for the first particle arrangement layer having a resin layer with an average thickness of 15 μm.
[0182] -Preparation of a film-shaped master mold for the first arrangement of thermally conductive particles-
[0183] First, a nickel plate with a thickness of 2 mm was prepared, and cylindrical protrusions (outer diameter 4 μm, height 4 μm, center-to-center distance 6 μm) with a hexagonal lattice pattern were formed in the 50 cm square area, and the surface density of the protrusions was 32,000 pieces / mm. 2 The transfer body master mold.
[0184] Next, a polyethylene terephthalate (PET) substrate film having a width of 50 cm and a thickness of 50 μm was prepared, and a photocurable resin composition containing 100 parts by weight of an acrylate resin (M208, manufactured by Toagosei Co., Ltd.) and 2 parts by weight of a photopolymerization initiator (IRGACURE 184, manufactured by BASF Japan Ltd.) was applied onto the PET substrate film so that the film thickness became 30 μm.
[0185] The obtained photocurable resin composition film was pressed against a nickel transfer master mold from its convex surface and heated by a high-pressure mercury lamp (1,000 mJ / cm 2 ), and irradiated with light from the PET substrate film side, thereby forming a photocurable resin layer in which the convex parts of the transfer master mold are transferred as concave parts. This operation is continuously repeated while aligning along the length direction of the PET substrate film, thereby obtaining a film-like master mold of about 10 m in which the convex parts of the transfer master mold are transferred as concave parts. In the obtained film-like master mold, the concave parts corresponding to the convex part pattern of the transfer master mold are arranged in a hexagonal lattice.
[0186] Next, Ag particles (manufactured by DOWA Electronics Co., Ltd., volume average particle size Dv: 1 μm) were prepared as first thermally conductive particles, and the first thermally conductive particles were scattered multiple times on the surface of the film-like master mold. Next, the first thermally conductive particles were wiped with a cloth, and the first thermally conductive particles were filled in the concave portions of the film-like master mold cut at 30 cm in the length direction.
[0187] -Transfer of the First Thermally Conductive Particles to the Resin Film for the First Particle Arrangement Layer-
[0188] Next, on the cut film-like master mold filled with the first thermally conductive particles under predetermined conditions, the first particle arrangement layer resin film is aligned and covered in a manner that the length in the longitudinal direction is uniform and the width direction includes the vicinity of the central part of the film-like master mold, and is pressed at 60°C and 0.5MPa to transfer the first thermally conductive particles. Furthermore, the insulating resin layer film is peeled off from the film-like master mold, and the first thermally conductive particles in the arranged state on the thermally conductive film are pressed (pressing conditions: 60°C to 70°C, 0.5MPa) to press the first particle arrangement layer resin film, and this is performed at 5 points of the cut film-like master mold, thereby producing a first particle arrangement layer forming sheet in which the first thermally conductive particles are buried in the arranged state.
[0189] <Preparation of the Second Particle Arrangement Layer Forming Sheet>
[0190] -Preparation of resin film for second particle arrangement layer-
[0191] A resin composition containing 56 parts by mass of an oxetane compound (4,4'-bis[(3-ethyl-3-oxetane)methoxymethyl]biphenyl, manufactured by UBE Co., Ltd.), 22 parts by mass of glutaric acid (manufactured by Tokyo Chemical Industry Co., Ltd.) and 22 parts by mass of a polyamide compound (M1276, manufactured by Arkema Co., Ltd.) was applied to a peeling film (PET38GS, manufactured by LINTEC Co., Ltd.) to produce a resin film for a second particle arrangement layer having a resin layer with an average thickness of 70 μm.
[0192] In Example 1, the second particle arrangement layer forming sheet was prepared in the same manner as in Example 1 except that the above-mentioned second particle arrangement layer resin film was used and the first thermally conductive particles were replaced by second thermally conductive particles 1 (Ag-coated Cu particles, manufactured by Fukuda Metal Foil Powder Industry Co., Ltd., with a volume average particle size Dv: 40 μm).
[0193] <Preparation of the third and fourth particle arrangement layer forming sheets>
[0194] -Preparation of the third and fourth particle arrangement layer resin films-
[0195] A resin composition containing 56 parts by mass of an oxetane compound (4,4'-bis[(3-ethyl-3-oxetane)methoxymethyl]biphenyl, manufactured by UBE Co., Ltd.), 22 parts by mass of glutaric acid (manufactured by Tokyo Chemical Industry Co., Ltd.) and 22 parts by mass of a polyamide compound (M1276, manufactured by Arkema Co., Ltd.) was applied to a peeling film (PET38GS, manufactured by LINTEC Co., Ltd.) to produce a resin film for the third and fourth particle arrangement layers having a resin layer with an average thickness of 20 μm.
[0196] In Example 1, the third and fourth particle array layer resin films are used, and the first thermally conductive particles are the first and second low melting point metal particles (Sn 42 Bi 58 Particles: manufactured by Mitsui Mining & Smelting Co., Ltd., volume average particle diameter Dv: 4 μm, melting point 139° C.) The third and fourth particle arrangement layer-formed sheets were prepared in the same manner as in Example 1 except for the above.
[0197] <Production of laminated body>
[0198] Between a 30mm×30mm×2mm substrate (silicon) and a 30mm×30mm×2mm opposing substrate (copper), the first particle arrangement layer forming sheet, the third particle arrangement layer forming sheet, the second particle arrangement layer forming sheet and the fourth particle arrangement layer forming sheet are stacked in sequence from the substrate (silicon) side, and after hot lamination at 80°C at predetermined positions, hot pressing is performed at 80°C for 15 minutes to produce the stacked body of Example 1.
[0199] (Example 2)
[0200] In Example 1, the second thermally conductive particles 1 (Ag-coated Cu particles, manufactured by Fukuda Metal Foil Powder Co., Ltd., with a volume average particle size Dv: 40 μm) were replaced with the second thermally conductive particles 2 (Cu particles, manufactured by Fukuda Metal Foil Powder Co., Ltd., with a volume average particle size Dv = 40 μm). Except for this, the second particle arrangement layer forming sheet was prepared in the same manner as in Example 1, and the laminated body of Example 2 was prepared in the same manner as in Example 1.
[0201] (Comparative Example 1)
[0202] A laminate of Comparative Example 1 was produced in the same manner as in Example 1 except that the first particle array layer forming sheet was not provided.
[0203] (Comparative Example 2)
[0204] A laminate of Comparative Example 2 was produced in the same manner as in Example 1 except that the second particle array layer forming sheet was not provided.
[0205] Next, thermal conductivity and reliability of each obtained laminate were evaluated as follows. The results are shown in Tables 1 and 2.
[0206] <Thermal conductivity>
[0207] The thermal resistance (°C·cm) of each obtained laminate was measured according to the method of ASTM-D5470. 2 / W). From the result, the thermal resistance of the cured product was calculated by subtracting the thermal resistance of the substrate and the opposing substrate. The thermal conductivity (W / m·K) was determined from the thermal resistance and the thickness of the cured product. The thermal conductivity was evaluated according to the following criteria.
[0208]
Evaluation criteria
[0209] ◎: Thermal conductivity 10W / m·K or more
[0210] ○: Thermal conductivity is 7W / m·K or more and less than 10W / m·K
[0211] ×: Thermal conductivity is less than 7W / m·K
[0212] <Reliability>
[0213] Each of the above-mentioned laminated bodies was placed in an environmental tester at 150° C. for 500 hours, and the thermal conductivity after the reliability test was measured. The reduction rate of the thermal conductivity from the initial value was obtained, and the reliability was evaluated according to the following criteria.
[0214]
Evaluation criteria
[0215] ◎: Relative to the initial thermal conductivity, the reduction rate is less than 10%
[0216] ○: Reduction rate relative to initial thermal conductivity is 10% or more and 30% or less
[0217] ×: Reduction rate relative to initial thermal conductivity is greater than 30%
[0218]
Table 1
[0219]
[0220]
Table 2
[0221]
[0222] Industrial Availability
[0223] The laminate of the present invention can achieve high thermal conductivity as a thermal interface material (TIM), and is therefore suitable for use in various electrical device peripherals such as CPUs, MPUs, power transistors, LEDs, and laser diodes, where temperature has an adverse effect on the efficiency and life of component operations.
[0224] This application claims priority based on Japanese Patent Application No. 2022-93020 filed with the Japan Patent Office on June 8, 2022, and cites all the contents described in the above application.
[0225] Explanation of symbols
[0226] 1 Thermal conductive sheet
[0227] 2 Cooling module
[0228] 2a Main side
[0229] 3Heating element (electronic components)
[0230] 3a Top
[0231] 5 Heat sink
[0232] 6 Wiring board
[0233] 7 Laminated body
[0234] 10, 10A, 10B laminate
[0235] 11 Base material
[0236] 121st particle arrangement layer
[0237] 13. The second particle arrangement layer
[0238] 14Third particle arrangement layer
[0239] 154th particle arrangement layer
[0240] 16 Opposing substrate
[0241] 17 No.1 Thermal Conductive Particles
[0242] 18. Second thermal conductive particles
[0243] 191st low melting point metal particles
[0244] 202nd low melting point metal particles
Claims
1. A laminate, characterized in that: have: Base material; On the substrate, a first particle arrangement layer is provided, wherein the first thermally conductive particles are arranged at predetermined intervals; as well as The second particle arrangement layer includes second heat-conductive particles on the first particle arrangement layer, wherein the second heat-conductive particles are arranged at predetermined intervals. A portion of the first heat-conductive particles included in the first particle arrangement layer is in contact with a portion of the second heat-conductive particles included in the second particle arrangement layer, and a volume average particle size of the first heat-conductive particles is smaller than a volume average particle size of the second heat-conductive particles. The substrate includes at least one selected from silicon, aluminum, tungsten, molybdenum, glass, a molding resin, stainless steel, and ceramics.
2. The laminate according to claim 1, A ratio (A:B) of a volume average particle size A of the first heat-conductive particles to a volume average particle size B of the second heat-conductive particles is 1:2 to 1:
50.
3. The laminate according to claim 1 or 2, The first thermally conductive particles have a volume average particle size of 0.3 μm or more and 30 μm or less.
4. The laminate according to claim 1 or 2, The second heat-conductive particles have a volume average particle size of 1 μm or more and 100 μm or less.
5. The laminate according to claim 1 or 2, A third particle arrangement layer including first low-melting-point metal particles arranged at predetermined intervals is provided between the substrate and the first particle arrangement layer.
6. The laminate according to claim 1 or 2, Between the first particle arrangement layer and the second particle arrangement layer, there is a fourth particle arrangement layer including second low-melting-point metal particles, wherein the second low-melting-point metal particles are arranged at predetermined intervals.
7. The laminate according to claim 1 or 2, The first heat-conductive particles and the second heat-conductive particles are at least any one of copper particles, silver-coated particles, and silver particles.
8. The laminate according to claim 5, The first low-melting-point metal particles include Sn and at least one selected from Bi, Ag, Cu, and In.
9. The laminate according to claim 6, The second low-melting-point metal particles include Sn and at least one selected from the group consisting of Bi, Ag, Cu, and In.
10. The laminate according to claim 1 or 2, On the second particle arrangement layer, there is an opposing substrate facing the substrate, The opposing substrate includes at least one selected from the group consisting of copper, gold, platinum, palladium, silver, zinc, iron, tin, nickel, magnesium, indium, and alloys thereof.
11. A method for producing a laminate, characterized in that: The process includes the following steps: a first particle arrangement layer forming step of forming a first particle arrangement layer including first thermally conductive particles arranged and spaced apart at predetermined intervals on a substrate; and a second particle arrangement layer forming step of forming a second particle arrangement layer including second heat conductive particles arranged and spaced apart at predetermined intervals on the first particle arrangement layer; The substrate includes at least one selected from silicon, aluminum, tungsten, molybdenum, glass, a molding resin, stainless steel, and ceramics.
Citation Information
Patent Citations
Thermal interface material based on composite thermal-conduction network of low-melting-point metals and thermal-conduction particles, and preparation method of thermal interface material
CN108912683A
Resin material and laminate
CN109415570A
Composite thermal interface materials, thermal interface components, and methods for making the same
US20190092994A1